2000
DOI: 10.1046/j.1365-2850.2000.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in community mental health nurses: findings from the all‐Wales stress study

Abstract: Stress and its outcomes are significant problems for mental health workers. Questionnaires were sent to 614 community mental health nurses (CMHNs) in Wales. Three hundred and one responded (49%). Of these, 283 completed the Maslach Burnout Inventory (MBI) (Maslach et al. 1996). Half of those who responded indicated that they were emotionally overextended and exhausted by their work. One quarter of respondents were found to possess negative attitudes towards their clients, and approximately one in seven experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0
13

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 19 publications
6
71
0
13
Order By: Relevance
“…These results corroborate Brazilian studies (De Marco et al, 2008;Ishara et al, 2014;Rebouças et al, 2007) and contradict those of international studies reporting high levels of dissatisfaction (Evans et al, 2006;Hannigan et al, 2000). The highest mean score concerned the relationship established with coworkers, while the mean scores concerning the service's infrastructure and working conditions were the lowest.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results corroborate Brazilian studies (De Marco et al, 2008;Ishara et al, 2014;Rebouças et al, 2007) and contradict those of international studies reporting high levels of dissatisfaction (Evans et al, 2006;Hannigan et al, 2000). The highest mean score concerned the relationship established with coworkers, while the mean scores concerning the service's infrastructure and working conditions were the lowest.…”
Section: Discussionsupporting
confidence: 83%
“…Various studies have assessed mental health services using satisfaction measures and most focused on patient satisfaction (Blenkiron & Hammill, 2003;Gani et al, 2011;Heckert, Teixeira, & Trindade, 2006;Holikatti et al, 2012;Kantorski et al, 2009;Silva, Bandeira, Scalon, & Quáglia, 2012), followed by that of healthcare providers (De Marco, Cítero, Moraes, & Nogueira-Martins, 2008;Evans et al, 2006;Hannigan, Edwards, Coyle, Fothergill, & Burnard, 2000;Ishara et al, 2014;Pelisoli, Moreira, & Kristensen, 2007;Rebouças et al, 2007). The satisfaction of families was the least studied (Bandeira et al, 2011;Perreault et al, 2011;Santos & Cardoso, 2014;Stengard, Honkonen, Koivisto, & Salokangas, 2000).…”
mentioning
confidence: 99%
“…The most common means of measuring prevalence of mental health problems in mental health nurses has been the use of versions of the General Health Questionnaire (GHQ) (Goldberg and Williams, 1988) (Johnson et al, 2011;Edwards et al, 2000;Fagin et al, 1996). Wall et al (1997), using the GHQ-12 on 11637 NHS staff, found psychiatric morbidity of 26.8% 3Age, experience and years overall, with 30% for male and 29% for female nurses.…”
Section: Prevalence Of Experience Of Mental Health Problems In Uk Mhnsmentioning
confidence: 99%
“…Wall et al (1997), using the GHQ-12 on 11637 NHS staff, found psychiatric morbidity of 26.8% 3Age, experience and years overall, with 30% for male and 29% for female nurses. Caseness in the UK has been reported at 42% for early career mental health nurses (Kipping, 2000), 41% for CPNs (Fagin et al, 1995;1996), 39% for CMHT staff (Johnson et al, 2011), 38% for CMHT staff (Walsh et al, 2002); 35% (Edwards et al, 2000), 31% and 27.9% for WBPNs (Fagin et al, 1995;1996), 30% for CMHT staff (Wykes, Stevens & Everitt, 1997), 29% for mental health trust staff (Johnson et al, 2011). More recently, Mark and Smith (2012) surveyed nurses accessed at random via the Royal College of Nursing (hence a similar target group to the one in the present study, albeit not mental health nurses), using the Hospital Anxiety and Depression Scale (HADS) (Zigmond and Snaith, 1983), and found 27.3% of nurses to meet the 'clinical cut-off for anxiety and depression.'…”
Section: Prevalence Of Experience Of Mental Health Problems In Uk Mhnsmentioning
confidence: 99%
“…More data are available on burnout (Maslach et al 2001), particularly for healthcare personnel Leiter and Harvie 1996). During the past two decades adverse work characteristics that increase the risk of burnout in healthcare professionals have been identified (Payne 2001;Hannigan et al 2000;Demerouti et al 2000). Burnout may ultimately lead to absenteeism, reduced job performance and an increased risk of psychosomatic or psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%